Antimicrobial resistance profiles of diarrhoeagenic Escherichia coli isolated from travellers returning to the UK, 2015–2017. Issue 7 (12th July 2020) - Boxall, Megan D.; Day, Martin R.; Greig, David R.; Jenkins, Claire
Abstract : Introduction. Diarrhoeagenic Escherichia coli (DEC) are difficult to distinguish from non-pathogenic commensal E. coli using traditional culture methods. The implementation of PCR targeting specific virulence genes characteristic of the five DEC pathotypes, has improved the detection of DEC in faecal specimens from patients with symptoms of gastrointestinal disease. Aim. Antimicrobial resistance (AMR) profiles of 660 strains of DEC isolated between 2015 and 2017 from UK travellers reporting symptoms of gastrointestinal disease were reviewed to look for evidence of emerging AMR associated with travellers' diarrhoea. Methodology. All isolates of DEC were sequenced, and sequence type, serotype, pathotype markers and AMR profiles were derived from the genome data. Results. A travel history was provided for 54.1 % (357/660) of cases, of which 77.0 % (275/357) reported travel outside the UK within 7 days of onset of symptoms, and 23.0 % (82/357) reported no travel in that time frame. Of the 660 strains of DEC in this study, 265 (40.2 %) samples were identified as EAEC, 48 (7.3 %) as EIEC, 61 (9.2 %) were ETEC and 286 (43.3 %) were EPEC. EPEC caused the highest percentage of infections in children (40.6 %) whilst the highest proportion of cases reporting recent travel were infected with ETEC (86.1 %). There were 390/660 (59.0 %) isolates resistant to at least one antimicrobial on the panel tested (EIEC, 81.3 %; ETEC, n =65.6 %; EAEC, n =73.2 %; EPEC, 40.9 %) and 265/660 (40.2 %) were multidrug-resistant (EIEC, 33.3 %; ETEC, 32.8 %; EAEC, 56.2 %; EPEC, 28.0 %). Genes conferring resistance to the beta-lactams and fluroquinolones were highest in the EAEC pathotype, 56.6 and 60.7%, respectively. Conclusions. Increasing MDR, along with resistance to the fluroquinolones and the third-generation cephalosporins, in DEC causing travellers' diarrhoea provides further evidence for the need to restrict the use of antimicrobial agents and continuous monitoring.